Age and Ebola viral load correlate with mortality and survival time in 288 Ebola virus disease patients. (January 2016) - Li, Jin; Duan, Hui-Juan; Chen, Hao-Yang; Ji, Ying-Jie; Zhang, Xin; Rong, Yi-Hui; Xu, Zhe; Sun, Li-Jian; Zhang, Ji-Yuan; Liu, Li-Ming; Jin, Bo; Zhang, Jian; et al.
Highlights: Common symptoms of Ebola virus disease (EVD) patients included fever, fatigue, abdominal pain, headache, and diarrhea. Compared with patients aged <18 years, those who were older than 40 had a higher probability of death. Patients with a viral load of >10 6 copies/ml had a higher case fatality rate than those with <10 6 copies/ml. Cox regression showed that age, log viral load, and the presence of diarrhea were correlated with mortality. Summary: Background: A Chinese medical team managed Ebola virus disease (EVD) patients in Sierra Leone from October 2014 to March 2015 and attended to 693 suspected patients, of whom 288 had confirmed disease. Methods: A retrospective study was conducted of the 288 patients with confirmed disease. Clinical symptoms, manifestations, and serum viral load were analyzed and compared among the different groups for mortality and survival time. Results: Among the 288 confirmed EVD patients (149 male and 139 female, median age 28 years, and median log viral load 6.68), 98 died, 36 recovered, and 154 were lost to follow-up. Common symptoms were fever (77.78%), fatigue (64.93%), abdominal pain (64.58%), headache (62.85%), and diarrhea (61.81%). Compared to patients aged < 18 years, those who were older than 40 years had a higher probability of death (odds ratio 2.855, p = 0.044). Patients with a viral load of >10 6 copies/ml had a higher case fatality rate than those with <10 6 copies/ml (odds ratio 3.095, p = 0.004). Cox regression showed that age, viral load, and the presence of diarrhea correlated with mortality. Conclusion: Patients with a high viral load, of older age, and with diarrhea had a higher mortality and shorter survival time.